Retrospective Matched Cohort Comparison of Prehospital Finger Thoracostomy and Needle Thoracostomy Performed by Ground Emergency Medical Services - Ciaraglia, Angelo; Smith, Alison; Axtman, Benjamin; Eastridge, Brian; Stewart, Ronald; Nicholson, Susannah; Jenkins, Donald (International Journal of Paramedicine, 2024)
Introduction: Tension pneumothorax related to chest trauma is a rapidly lethal condition that requires immediate treatment, often prior to arrival at definitive care. Recent concerns regarding the safety and efficacy of needle thoracostomy (NT) have led to alternatives. Finger thoracostomy (FT) is a potential life-saving treatment performed by prehospital providers as an alternative to NT. We hypothesize that FT has improved rates of prehospital thoracic decompression and is a safe alternative to NT. Materials and Methods: Retrospective cohort study of consecutive adult trauma patients presenting to a Level 1 trauma center who sustained chest trauma. A matched cohort of patients who underwent prehospital FT was compared to patients who underwent prehospital NT for thoracic decompression. Wilcoxon Rank Sum Test and Chi-Squared Analyses were performed for comparison of prehospital and in-hospital outcome variables. Results: 34 patients were compared, of which 15 underwent prehospital FT and 19 underwent prehospital needle thoracostomy NT. Groups were well matched in terms of demographics and injury characteristics. No difference in transport times were observed. All 15 patients in the FT group sustained cardiac arrest prior to arrival with 20% achieving return of spontaneous circulation (ROSC), while 6/19 NT patients arrived in cardiac arrest, with 66.7% achieving ROSC (p = 0.04). The rate of successful intrathoracic decompression was higher in the FT group (93.3% vs 47.4%, p<0.001). The NT group had a higher rate of chest tube placement (p=0.005). In-hospital mortality was not different between the two groups (p=0.213). Conclusions: FT is a viable alternative to NT for emergent thoracic decompression. The higher success rate of intrathoracic decompression supports the use of FT as an alternative to NT for prehospital tension pneumothorax, although future studies are needed establish superiority and further evaluate mortality and in-hospital outcomes.